1999
DOI: 10.1016/s1010-7940(99)00081-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ‘renal-dose’ dopamine on renal tubular function following cardiac surgery: assessed by measuring retinol binding protein (RBP)1

Abstract: Dopamine given at 'renal-dose' appears to offer no renal protection in patients with normal heart and kidney functions undergoing elective coronary surgery. On the contrary, it exacerbates the severity of renal tubular injury during the early postoperative period. Based on these findings we do not recommend the use of dopamine for routine renal prophylaxis in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 20 publications
0
37
1
Order By: Relevance
“…Some authors have reported an increase of urine output after dopamine administration 8,28 while others described no effect. [29][30][31] In our study, cumulative urine output was not increased by dopamine, contrary to diltiazem. More specific markers of renal integrity are necessary to completely assess the worth of different renal protective strategies.…”
Section: Discussioncontrasting
confidence: 46%
“…Some authors have reported an increase of urine output after dopamine administration 8,28 while others described no effect. [29][30][31] In our study, cumulative urine output was not increased by dopamine, contrary to diltiazem. More specific markers of renal integrity are necessary to completely assess the worth of different renal protective strategies.…”
Section: Discussioncontrasting
confidence: 46%
“…Dopamine Agonists. Despite the known ability of dopamine to increase renal blood flow at low doses, multiple studies of dopamine in cardiac and noncardiac surgical populations have failed to show a benefit in terms of either mortality or renal function (195)(196)(197)(198). Fenoldopam, a selective DA 1 agonist, has showed some promise in small studies (not all of them randomized) (199)(200)(201)(202), although this has not been universal (203).…”
Section: Current and Future Pharmacologic Strategiesmentioning
confidence: 99%
“…Many strategies have been proposed for preventing ARF, most of which focus on enhancing renal perfusion or reducing renal oxygen consumption [5], but no strategy has irrefutably been of benefit in preventing ARF. Mannitol, an osmotic diuretic, was the earliest pharmacological agent used for prophylaxis of ARF following cardiac surgery [6], but its usefulness has been debated ever since.…”
mentioning
confidence: 99%